2007
DOI: 10.1097/mao.0b013e3180686e4a
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q 10 and Cardiovascular Risk Factors in Idiopathic Sudden Sensorineural Hearing Loss Patients

Abstract: The studies regarding the role of cardiovascular risk factors in ISSNHL are not conclusive. This is the first report regarding the association of ISSNHL and low serum levels of the antioxidant CoQ. Further studies are needed to investigate the role of antioxidants, including CoQ, in ISSNHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Previous studies have shown that altering the redox status of the cochlea affects hearing capacity, in particular caloric restriction has been shown to reduce presbycusis and attenuate oxidative damage . Other studies, in the context of noise induced and sudden sensorineural hearing loss, have determined that a low dose of CoQ, similar to the one used in the current study, has the ability to improve hearing loss in guinea pigs (Fetoni et al 2009) and humans (Cadoni et al 2007). Supplementation with high CoQ led to further impairments of auditory efficiency in the current study as well as in the lifelong supplementation of CoQ (Sumien et al 2009); perhaps such high dose led to increased damage and/or mitochondrial derangement, enhancing the effect of aging on the auditory system.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have shown that altering the redox status of the cochlea affects hearing capacity, in particular caloric restriction has been shown to reduce presbycusis and attenuate oxidative damage . Other studies, in the context of noise induced and sudden sensorineural hearing loss, have determined that a low dose of CoQ, similar to the one used in the current study, has the ability to improve hearing loss in guinea pigs (Fetoni et al 2009) and humans (Cadoni et al 2007). Supplementation with high CoQ led to further impairments of auditory efficiency in the current study as well as in the lifelong supplementation of CoQ (Sumien et al 2009); perhaps such high dose led to increased damage and/or mitochondrial derangement, enhancing the effect of aging on the auditory system.…”
Section: Discussionmentioning
confidence: 75%
“…Forty‐nine articles were retrieved for full‐text review, 10 of which were written in a foreign language. Twenty‐two articles were included in the final review 10–31. None of the foreign language articles were included as they failed to meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…None of the foreign language articles were included as they failed to meet the inclusion criteria. Seventeen studies investigated potential medical risk factors for SSNHL 10–12, 14, 16–21, 23–25, 26, 28–30. Eleven studies examined the genetic risk factors that may predispose patients to develop SSNHL 14, 17–19, 21–24, 27, 29, 31.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Q-TER Ò consists of a mixture of maltodextrin, acting as a carrier of CoQ10 molecules (10% w/w), and sucrester, which serves as bioactivator [7]. Compared with native CoQ10, the resulting multicomposite is about 200 times more soluble in water: this allows a greater bioavailability and an improved chemical stability compared with the native form [8]. Q-TER Ò is manufactured using an industrially available native CoQ10 (Kaneka Pharma Europe, Brussels, Belgium).…”
Section: Methodsmentioning
confidence: 99%